2000
DOI: 10.1007/s005850000279
|View full text |Cite
|
Sign up to set email alerts
|

Wind-induced baroclinic response of Lake Constance

Abstract: We present results of various circulation scenarios for the wind-induced three-dimensional currents in Lake Constance, obtained with the aid of a semi-spectral semi-implicit ®nite dierence code developed in Haidvogel et al. and Wang and Hutter. Internal Kelvin and PoincareÂ-type oscillations are demonstrated in the numerical results, whose periods depend upon the strati®cation and the geometry of the basin and agree well with measured data. By solving the eigenvalue problem of the linearized shallow water equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…There is previous numerical evidence of internal Poincaré waves being locked to some features of the basin (e.g., Wang et al 2000) and of internal natural modes with a multicellular horizontal structure (Schwab 1977;Lemmin et al 2005); we offer here a dynamical explanation for their occurrence in terms of the dispersion relationships for circular basins developed by Antenucci and Imberger (2001). The structure of the 21ЊC isopycnal velocity of the 10.5-h-period wave (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…There is previous numerical evidence of internal Poincaré waves being locked to some features of the basin (e.g., Wang et al 2000) and of internal natural modes with a multicellular horizontal structure (Schwab 1977;Lemmin et al 2005); we offer here a dynamical explanation for their occurrence in terms of the dispersion relationships for circular basins developed by Antenucci and Imberger (2001). The structure of the 21ЊC isopycnal velocity of the 10.5-h-period wave (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…An asymmetric basin shape breaks the symmetry of the velocity field in the upper layer and increases the maximum correlation between the upper-layer velocity and wind stress, allowing preferential excitation of higher horizontal modes even by spatially uniform wind. This would explain why internal waves of higher horizontal modes have been observed in other lakes with irregular shape (e.g., Wang et al 2000;Lemmin et al 2005).…”
Section: Discussionmentioning
confidence: 88%
“…In real basins, irregular bathymetry modifies the horizontal structure of a Poincaré wave by localizing the wave (Wang et al 2000) or by introducing an accompanying cyclonic cell (Gó mez-Giraldo et al 2006); whereas the horizontal structure of a Kelvin wave appears to be insensitive to basin irregularities (Mortimer 1974;Gó mezGiraldo et al 2006). Recently Gó mez- Giraldo et al (2006) analyzed an internal wave consisting of an anticyclonic cell and a cyclonic cell in Lake Kinneret and suggested that the cells were governed by the dispersion relationship of Poincaré and Kelvin waves, respectively, in a circular (or elliptic) basin.…”
mentioning
confidence: 99%
“…Poincaré vertical mode-one waves in Upper Lake Constance have a more local character (Wang et al 2000), with periods in autumn typically around 12 h in the central and eastern main basin (Hollan 1974;Heinz 1995;Wang et al 2000), 9 h at the western end of the main basin (Heinz 1995;Wang et al 2000), and 4 h in Lake Ü berlingen (Hollan 1974;Bäuerle 1994;Wang et al 2000). Little seems to be known about basin-scale internal waves of higher vertical modes.…”
Section: Basin-scale Internal Waves-basin-scale Internal Waves Inmentioning
confidence: 99%